Enhancing Coastal Students' Well-Being: The Role of Pro-Environmental Behavior, Place Attachment, and Self-Efficacy - Eva Precilia Lukman; Siti Nurbayani K; Shahibah Yuliani (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
Subjective well-being among students in coastal schools can be influenced by pro-environmental behavior, place attachment, and self-efficacy. This study aims to analyze the contributions of these three factors to students' subjective well-being in the Thousand Islands region. Employing a quantitative approach, the research utilizes a survey method and explanatory survey design. The study population comprises 996 students from seven junior high schools in the Thousand Islands, with a sample of 285 students selected through simple random sampling. Data were collected using a validated and reliable questionnaire measuring pro-environmental behavior, place attachment, self-efficacy, and subjective well-being. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to assess the relationships between exogenous variables (pro-environmental behavior, place attachment, self-efficacy) and endogenous variables (subjective well-being). The results indicate that pro-environmental behavior, place attachment, and self-efficacy significantly positively affect students' subjective well-being. These findings highlight the importance of enhancing place attachment and self-efficacy to maximize the positive impact of pro-environmental behavior on students' well-being. Recommendations include developing environmental education programs that strengthen students' attachment to their school environment and enhance their self-efficacy in pro-environmental behavior.Keywords: Coastal schools, environmental behavior, Â place attachment,Â self-efficacy.